Needs Analysis of Electronic Student Worksheets to Practice 4C Skills - Maulana, Yusup; Sopandi, Wahyu (Jurnal Basicedu, 2022)
This study describes the needs of electronic student worksheets (e-LKM) that practice 21st century skills: critical thinking, collaboration, creativity, and communication (4C). This qualitative descriptive study involved 16 lecturers from 7 universities in Indonesia. The research instrument is a questionnaire that two education experts have validated. The questionnaire was distributed openly through the lecturers and students' WhatsApp groups. The data was collected in the form of questionnaires supported by data from 25 student worksheets collected from lecturers who filled out the questionnaires and were spread on the internet. Questionnaire data is processed using the percentage technique while LKM data is analyzed based on LKM standards, electronic or conventional based, whether or not it supports specific learning models and the emergence of 4C skills. The results showed that many student worksheets did not follow the standard, were not electronic-based, did not support specific learning models, and did not train 4C skills. This research indicates the need to develop electronic student worksheets that practice 4C skills in pandemic situations and teach digital literacy and 21st-century skills.